Texts Of Yildizname, Falname And Taliname In The Context Of Ottoman Fortune-Telling Tradition - Gür, Nagihan (Milli Folklor Dergisi, Pk 336, Ankara, Yenisehr 06420, Turkey, 2012)
The curiosity of mankind to learn about the future is also a part of his effort to give meaning to universe. This curiosity has led man, who for centuries aimed to seek the opportunity to learn about the future, to new experiences and caused the development of new fortune-telling methods as to have new angles in the pursuit of future events. These methods, which were presumed to originate from Mesopotamia and transferred to Greek and Sanskrit in Babylon era, spread from Western Europe to China, and hence from ancient times to Middle age and to present time at last. The purpose of this essay is to present the texts for fortune-telling with utmost importance in the written culture of the Ottoman times. For the very reason, the unique fortune-telling tradition which has survived until today and the rituals generating from this tradition are to be concurrently dealt with. Following the searches took place in Suleymaniye Library, Millet Manuscripts Library, and the National Library of Turkey in Ankara, a number of texts have been attained under the titles; yildizname, talinameand falname. Within the scope of this research, the characteristics of various texts under the headings of psychology, metaphysics, fortune-telling, falname, astronomy, astrology, occultism, and dreams have been analysed. Besides, the literature of fortune-telling has been examined. Through a deep analysis of the aforementioned texts, it is also aimed to bring in where the tradition of fortune-telling stands, what the expectation of community is from these texts, and furthermore, what the questions and applications are directed to these texts in order to satisfy curiosity and desire to know the future. Within this framework, methods and experimentations of fortune-telling literature, which have gained prevalence in the Ottoman period, have been examined, and therefore the systematic of this tradition has been under examination. Where fortune literature stands within the framework of Islamic tradition has also been touched upon. Hence, the construct of these texts has evaluated under the light of Islamic fatalist understanding.
Keywords: Ottoman; fortune-telling; yildizname; falname; taliname; Osmanlı; falcılık; yıldızname